Nonlinear Neutral Caputo q-Fractional Difference Equations with Applications to Lotka-Volterra Neutral Model - Mesmouli, Mouataz Billah; Ardjouni, Abdelouaheb (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we consider nonlinear neutral q-fractional difference equations which have important applications in many domains of life sciences. By using the Krasnoselskii fixed point theorem, sufficient conditions for the existence of solutions are established, also the uniqueness of solutions is given. As an application of the main theorems, we provide the existence and uniqueness of the discrete q-fractional Lotka-Volterra model of neutral type. Our main theorems are important results because are extend and generalize the results in the literature.